Premature senescence and increased TGFβ signaling in the absence of Tgif1. - Brad J Zerlanko (Public Library of Science (PLoS), 2012)
Transforming growth factor β (TGFβ) signaling regulates cell cycle progression in several cell types, primarily by inducing a G1 cell cycle arrest. Tgif1 is a transcriptional corepressor that limits TGFβ responsive gene expression. Here we demonstrate that primary mouse embryo fibroblasts (MEFs) lacking Tgif1 proliferate slowly, accumulate increased levels of DNA damage, and senesce prematurely. We also provide evidence that the effects of loss of Tgif1 on proliferation and senescence are not limited to primary cells. The increased DNA damage in Tgif1 null MEFs can be partially reversed by culturing cells at physiological oxygen levels, and growth in normoxic conditions also partially rescues the proliferation defect, suggesting that in the absence of Tgif1 primary MEFs are less able to cope with elevated levels of oxidative stress. Additionally, we show that Tgif1 null MEFs are more sensitive to TGFβ-mediated growth inhibition, and that treatment with a TGFβ receptor kinase inhibitor increases proliferation of Tgif1 null MEFs. Conversely, persistent treatment of wild type cells with low levels of TGFβ slows proliferation and induces senescence, suggesting that TGFβ signaling also contributes to cellular senescence. We suggest that in the absence of Tgif1, a persistent increase in TGFβ responsive transcription and a reduced ability to deal with hyperoxic stress result in premature senescence in primary MEFs.